2016
DOI: 10.1108/bfj-06-2015-0226
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance of food nanotechnology in Italy

Abstract: Purpose – The purpose of this paper is to investigate attitudes of Italian consumers towards a set of applications of nanotechnology in the food domain. The chief goal is to identify the main factors influencing the willingness to buy nanofoods (WTBN), distinguishing between factors related to the products, in terms of perceived risks and benefits and psychological factors. Design/methodology/approach – A questionnaire was administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“…For example, respondents who hold a skeptical view of biotechnology companies were less likely to consume nutritionally enhanced GM cereals than those who trusted biotechnology companies (Onyango & Nayga, ). Attitude toward product or technology: Several studies found evidence that general attitude toward product or technology (innovation) is the most important explanatory attitudinal factor for novel food technology evaluations. This relationship was primarily positive (for example, with respect to GM: Costa‐Font & Gil, ; Laros & Steenkamp, ; Spence & Townsend, ; fortification: Carrillo, Prado‐Gascó, Fiszman, & Varela, ; Cranfield, Henson, & Masakure, ; Krutulyte et al., ; and nanotechnology: Cook & Fairweather, ; Kim & Kim, ; Sodano, Gorgitano, Verneau, & Vitale, ). As illustrated in Figure , attitude toward product or technology (innovation) is significantly influenced by information assessment.…”
Section: Results Of the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, respondents who hold a skeptical view of biotechnology companies were less likely to consume nutritionally enhanced GM cereals than those who trusted biotechnology companies (Onyango & Nayga, ). Attitude toward product or technology: Several studies found evidence that general attitude toward product or technology (innovation) is the most important explanatory attitudinal factor for novel food technology evaluations. This relationship was primarily positive (for example, with respect to GM: Costa‐Font & Gil, ; Laros & Steenkamp, ; Spence & Townsend, ; fortification: Carrillo, Prado‐Gascó, Fiszman, & Varela, ; Cranfield, Henson, & Masakure, ; Krutulyte et al., ; and nanotechnology: Cook & Fairweather, ; Kim & Kim, ; Sodano, Gorgitano, Verneau, & Vitale, ). As illustrated in Figure , attitude toward product or technology (innovation) is significantly influenced by information assessment.…”
Section: Results Of the Reviewmentioning
confidence: 99%
“…Respondents for whom naturalness of food was important perceived more risks to be associated with nanotechnology compared to respondents who considered naturalness of foods to be less important (Siegrist et al., ). Concerning perceived healthiness, this attribute had a positive influence on purchase intention for functional food (Dobrenova, Grabner‐Kräuter, & Terlutter, ), GM food (Hu, Adamowicz, & Veeman, ), and food nanotechnology (Sodano et al., ). Figure shows that quality perception of the product mediates information assessment. Impact on health: Regarding impact on health, studies can be distinguished based on how a variable was conceptualized.…”
Section: Results Of the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of FTNS has been mostly limited to developed countries: Australia [8,9], Italy [10,11,20,[25][26][27], Canada [7,22], South Korea [28] and Poland [29]. In the case of developing countries we find Brazil [12], Uganda [13] and Chile [30] with variability in the results between both contexts (developed and developing countries) without reaching consensus; therefore, possibilities are still being explored.…”
Section: Food Technology Neophobiamentioning
confidence: 99%
“…The evidence on studies in Mexico is non-existent, therefore, this research is one of the first to provide guidelines in this line and allows to know the preferences of the Mexican consumer towards the products elaborated with food technology. The most commonly used food technologies in recent studies have been: pasteurized fruit juice, high-pressure fruit juice processing, salads in modified atmosphere packaging, triploid prawns, genetically modified oilseeds and bioactive yoghurt [8,9], processed organic food, light and frozen [10,11,20,25] and the use of nanotechnology [12,22,26,28], vacuum packaging [7], fortified and functional products [27,29]. Some findings that have been obtained in a comparative way indicate that Brazilians are less neo-phobic than Australians and Canadians [9,12,22], the participants are unfamiliar with genetically modified food and nanotechnology, influenced by risk and perceived benefit as well as the level of confidence in the food industry [12,26], there is also a predictive effect between ethical values and ecological awareness with the intention of buying genetically modified food [28].…”
Section: Food Technology Neophobiamentioning
confidence: 99%